Effects of life cycle and leaves location on gene expression and glycoside biosynthesis pathway in Stevia rebaudiana Bertoni - Ghaheri, Matin; Adibrad, Elaheh; Safavi, Seyed Mehdi; Kahrizi, Danial; Soroush, Ali; Muhammadi, Saare; Ghorbani, Tayebeh; Sabzevari, Ali; Ansarypour, Zahra; Rahmanian, Elham (Cellular and Molecular Biology, 2018)
Stevia rebaudiana Bertoni is One of the most important biologically sourced and low-calorie sweeteners that known as "Sweet Weed”. It contains steviol glycosides that they are about 200-300 times sweeter than sucrose. Tissue culture is the best method with high efficiency that can overcome to problems of traditional methods, and it is the most useful tools for studying stress tolerance mechanisms under in vitro conditions to obtain drought tolerance. In the present research, we investigated the impact of life cycle, leaves location and the harvesting time on expression of UGT74G1 and UGT76G1 as well as steviol glycosides accumulation. The highest gene expression of both UGT74G1 and UGT76G1 (207.677 and 208.396 Total Lab unit, respectively) was observed in young leaves in the second vegetative year. Also, the highest amount of stevioside accumulation (13.04) was due to the old leaves in vegetative stage which had significant differences with other effects whereas the lowest accumulation (7.47) was seen at young leaves at vegetative stage. Interestingly, the highest level of rebaudioside a production (15.74) was occurred at the young leaves at vegetative stage. There was significant differences between life cycle and leaves location on steviol glycoside production in stevia.